LA CHAKANA Y LA CRUZ CRISTIANA: RITUALES, RELIGIÓN, FIESTAS, IDEOLOGÍAS Y SIMBOLOGÍAS EN LOS CONJUNTOS DE SIKURIS URBANOS - Sánchez Huaringa, Carlos Daniel (2017)
The Feast of the Crosses has an unusual importance in the plateau and this same one has been recreated by the urban groups of sikuris in Lima from the decade of the 80 onwards. It is one of the most anticipated religious festivals by this urban movement that is characterized by its ideological discourses of the Marxist left conjugated with Andean utopia. These bear as central element of the feast and of veneration to the Christian cross and the Andean cross called chakana.